Evaluating the association of common UBE2Z variants with coronary artery disease in an Iranian population - Bastami, M; Ghaderian, S M; Omrani, M D; Mirfakhraie, R; Nariman-Saleh-Fam, Z; Mansoori, Y; Masotti, A (Cellular and Molecular Biology, 2015)
Coronary artery disease (CAD) is the leading cause of cardiovascular mortality worldwide. Genome-wide association studies have discovered several variants associated with CAD. Notably, a recent study has identified UBE2Z rs46522 at 17q21.32 as a CAD-susceptibility variant in Europeans. However, association of this locus with CAD in non-Europeans has not been investigated. Herein, we evaluated the contribution of rs46522 and a variant in high linkage disequilibrium in UBE2Z 3'-UTR (rs1057897) to the CAD susceptibility by performing association study in an Iranian population. This study recruited 300 angiographically-confirmed CAD patients and 300 asymptomatic controls. Genotypes were determined by TaqMan genotyping assay. Multivariate logistic regression analysis revealed that rs46522 was associated with the susceptibility to CAD assuming codominant [TT vs. CC: 2.68 (1.36-5.31), P: 1.1717e-2], dominant [CT+TT vs. CC: 1.74 (1.12-2.69), P: 1.2675e-2], recessive [TT vs. CC+CT: 2.12 (1.13-3.98), P: 1.9369e-2] and log-additive [1.61 (1.17-2.21), P: 2.967e-3] models. However, no association was observed for rs1057897 under any genetic models. In conclusion, we provide the first evidence for association of rs46522 with the susceptibility to CAD in an Iranian population and discussed about regulatory potential and functional role of the studied variants to provide clues for its association with CAD and promote further research.